Directed Synthesis of Nanoporous Carbons from Task‐Specific Ionic Liquid Precursors for the Adsorption of CO2. Issue 12 (31st July 2014) - Mahurin, Shannon M.; Fulvio, Pasquale F.; Hillesheim, Patrick C.; Nelson, Kimberly M.; Veith, Gabriel M.; Dai, Sheng
Abstract Postcombustion CO2 capture has become a key component of greenhouse‐gas reduction as anthropogenic emissions continue to impact the environment. We report a one‐step synthesis of porous carbon materials using a series of task‐specific ionic liquids for the adsorption of CO2. By varying the structure of the ionic liquid precursor, we were able to control pore architecture and surface functional groups of the carbon materials in this one‐step synthesis process leading to adsorbents with high CO2 sorption capacities (up to 4.067 mmol g−1) at 0 °C and 1 bar. Added nitrogen functional groups led to high CO2/N2 adsorption‐selectivity values ranging from 20 to 37 whereas simultaneously the interaction energy was enhanced relative to carbon materials with no added nitrogen.